Modulation of Immune Response by Gold Nanoparticles Intramuscular Injection to Rats - Mohammed Abbas Farman; Walaa Najm Abood (International Journal of Medical Toxicology and Legal Medicine, 2024)
Gold nanoparticles (GNPs) are an innovative chemical compound, their size is between 1-100 nm. These metal nanoparticles (NPs) exhibit exceptional properties entirely different from their larger sizes. The huge surface area, diversity of shape and size, stability, loaded ability, ease of creation and biocompatibility, making them valuable materials used in pharmacological applications. In addition. GNPs characteristics and their surface modification can modify toxicity and biodistribution. The current study aims to understand enhanced immune response by intramuscular (IM) injection of gold nanoparticles into rats. GNPs were IM injected into rats once at different doses. On the 15th day, samples from all rats were collected. The results revealed no toxic signs. Gold nanoparticles made a significant elevation of the level of antioxidant enzymes comprising superoxide dismutase(SOD) and catalase (CAT), whereas the level of oxidative stress marker Malondialdehyde (MDA) decreased in the injected groups at dose dependent manner when compared with the non-injected control group. Moreover, GNPs exhibit a modulation effect through enhanced immune cell activation via elevation of the level of CD4 and CD8 along with elevation of the level of TNF-α in the injection groups at dose dependent manner when compared with the non-injected control group.